Natural variation, differentiation, and genetic trade‐offs of ecophysiological traits in response to water limitation in Brachypodium distachyon and its descendent allotetraploid B. hybridum (Poaceae). (28th September 2015) - Manzaneda, Antonio J.; Rey, Pedro J.; Anderson, Jill T.; Raskin, Evan; Weiss‐Lehman, Christopher; Mitchell‐Olds, Thomas
<x xml:space="preserve">Abstract</x> Differences in tolerance to water stress may underlie ecological divergence of closely related ploidy lineages. However, the mechanistic basis of physiological variation governing ecogeographical cytotype segregation is not well understood. Here, using Brachypodium distachyon and its derived allotetraploid B. hybridum as model, we test the hypothesis that, for heteroploid annuals, ecological divergence of polyploids in drier environments is based on trait differentiation enabling drought escape. We demonstrate that under water limitation allotetraploids maintain higher photosynthesis and stomatal conductance and show earlier flowering than diploids, concordant with a drought‐escape strategy to cope with water stress. Increased heterozygosity and greater genetic variability and plasticity of polyploids could confer a superior adaptive capability. Consistent with these predictions, we document (1) greater standing within‐population genetic variation in water‐use efficiency (WUE) and flowering time in allotetraploids, and (2) the existence of (nonlinear) environmental clines in physiology across allotetraploid populations. Increased gas exchange and diminished WUE occurred at the driest end of the gradient, consistent with a drought‐escape strategy. Finally, we found that allotetraploids showed weaker genetic correlations than diploids congruous with the expectation of relaxed pleiotropic constraints in polyploids. Our results suggest evolutionary divergence of ecophysiological traits in each ploidy lineage.